Study of Bendo Sap (Artocarpus Elasticus Reinw) Polyurethane Adhesive on Modified Asphalt through Marshall Testing - Adiansyah Adiansyah; Tamrin Tamrin; Marpongahtun Marpongahtun; Sovia Lenny; Lua Shun Kuang; Ronn Goei (Pandawa Institute, 2026)
Bendo latex–based polyurethane (BD–PU) adhesive demonstrates strong potential as a bio-based modifier for improving asphalt performance and providing a sustainable alternative to petroleum-derived polymers. The novelty of this study lies in the utilization of bendo latex as a locally sourced renewable feedstock for polyurethane synthesis and its direct application as an asphalt modifier, which remains largely unexplored compared to conventional petroleum-based or partially bio-based polyurethane systems. In this work, bendo latex was converted into polyol via controlled condensation and addition reactions, followed by blending with polyethylene glycol (PEG 1000) and reaction with toluene diisocyanate (TDI) to produce BD–PU adhesive. The synthesized polyurethane exhibited mechanical properties comparable to conventional isocyanate-based polymers, confirming its suitability for asphalt modification. At the optimum BD–PU content of 20 wt%, the modified asphalt demonstrated a Marshall stability of 27.6 kN, a flow value of 4.5 mm, and a stiffness of 6.5 kN/mm. It represents a significant improvement over the control asphalt, with a 75% increase in Marshall stability and an 85% enhancement in stiffness, indicating markedly improved resistance to permanent deformation. These improvements are attributed to the formation of a crosslinked polyurethane network that enhances interfacial bonding between asphalt and aggregates, resulting in improved load distribution and structural integrity. Compared to previously reported polyurethane-modified asphalt systems, this study offers a key contribution by (i) introducing a fully bio-based polyol derived from bendo latex, (ii) demonstrating competitive or superior mechanical performance, and (iii) promoting the use of locally available renewable resources for sustainable infrastructure materials. Overall, the findings highlight the significant potential of BD–PU as an eco-friendly and high-performance asphalt modifier, supporting the development of more durable and sustainable road construction materials.